The Concepts of Commercial (Trade) Law in the Legal Doctrine of Russia and Foreign Countries - AMVROSOVA, Olga Nikolaevna; ATAYAN, Gayane Yuryevna; KASEVICH, Ekaterina Viktorovna; STANKEVICH, Galina Viktorovna; DURNEVA, Polina Nikolaevna (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
The problems of the formation and development of commercial (trade) law concepts are studied in this article. The stages of the formation of the commercial (trade) law in Europe and America as well as the commercial law doctrines in the Roman-Germanic and Anglo-American legal systems are studied herein. Particular attention is paid to the dualism of private law as the starting point in the formation and development of commercial (trade) law; the methodological and epistemological bases of the formation of the conceptual framework of commercial (trade) law are shown. For the purposes of indication of the boundaries of public and private law, the ideas of the subject matter and the method of legal regulation are reproduced. The novelty of the study is determined by the fact that the etymological, the legal and technical, the political and legal reviews of the problem, determination the differentiation of the concepts, as well as the use of commercial concepts and borrowed terms by the legislator, are justified herein. The comparative historical and comparative legal analysis of these concepts in different countries is carried on in this paper.